The Impact of the Presidency of Donald Trump on American Jewry and Israel - Windmueller, Steven F. (Purdue University Press, 2021)
The Trump presidency has resulted in a fundamentally disruptive moment in this nation's political culture. Not only were there different policy options and directions, but the cultural artifacts of politics changed because of how this president dramatically challenged the existing norms of political behavior and action. As we have shifted from a period of American liberalism to a time of political populism, deep fissures are dividing Americans in general and Jews in particular.The Impact of the Presidency of Donald Trump on American Jewry and Israel unpacks President Donald Trump's distinctive and unique relationship with the American Jewish community and the State of Israel. Addressing the various dimensions of his personal and political connections with Jews and Israel, this publication is designed to provide an assessment of how the Trump presidency has influenced and altered American Jewish political behavior. Writers from different backgrounds and political orientations bring a broad range of perspectives designed to examine various aspects of this presidency, including Trump's particular impact on Israel-US relations, his special connection with Orthodox Jews, and his complex and uneven relationship with Jewish Republicans.For liberal American Jews, these four years represented a fundamental revolution, overturning and challenging much that a generation of activists had fought to achieve and protect. For Trump's supporters, it afforded them an opportunity to advance their priorities, while joining the forty-fifth president in changing the American political landscape. The "Trump effect" will extend well beyond his four-year tenure, creating an environment that has fomented the politics of hate and exposed a deeply embedded presence of anti-Semitism. How Americans understand this moment in time and the ways society will adapt can be reflected through the prism of the Jewish encounter with Trumpism that this volume seeks to explore.